Perspektif Peserta Didik Abad 21: Relevansinya Dengan Pemikiran Imam Al-Ghazali Dalam Kitab Ayyuhal-Walad - Moh. Faizin; Maslihan Maslihan; Afi Rizqiyah (Jurnal Keislaman, 2023)
The era of digitalization has a real and broad effect from various walks of life, one of which demands in governance and the education system is clear evidence that this era is a new challenge in the world of education. Education is expected to be able to produce full quality human seed products, which are called 21st century competencies. 21st century competence is the main ability that must be pocketed by students in order to collaborate in real life in the 21st century. In the 21st century, the challenge is given to be able to create education that can participate in producing thinkers who are qualified in the development of economic and social order and are aware of how to become a decent citizen of the world in the 21st century. This study aims to describe 21st century students and look for relationships or relevance to Al Ghazali's thoughts regarding students in the book of Ayyuhal-Walad. The research method applied is descriptive qualitative. The results of the study indicate that Imam al-Ghazali's thoughts in his book, have relevance to the perspectives of 21st century students related to character education until now the main focus in education. and the 21st century teaches them to judge the good and the bad of all things. In accordance with the thoughts of Imam Al Ghazali in his book Ayyuhal-Walad which contains advice and suggestions to do good things and consider bad things.